The Effectiveness of Art Therapy for Anxiety in Adult Women: A Randomized Controlled Trial - Abbing, Annemarie; Baars, Erik W.; de Sonneville, Leo; Ponstein, Anne S.; Swaab, Hanna (Frontiers in Psychology, 2019)
Objectives: Art therapy as a treatment option for anxiety is regularly employed in clinical practice, but scientific evidence for its effectiveness is lacking, since this intervention has hardly been studied. The aim was to study the effectiveness of art therapy (AT) on anxiety in adult women. The specific type of AT studied was anthroposophic art therapy. Methods: a RCT comparing AT versus a waiting list (WL) condition on anxiety symptom severity, quality of life and emotion regulation. Factors influencing treatment outcome were additionally explored. Participants were women, aged 18-65 years, diagnosed with generalized anxiety disorder, social anxiety disorder or panic disorder, with moderate to severe anxiety symptoms. The trial was registered in the Dutch Trial Registration (NTR28143). Results: 59 women were included, of which 47 completed the trial. Both per-protocol and intention-to treat analyses demonstrated effectiveness of AT compared to WL, showing a reduction in anxiety, an increase in subjective quality of life (both with large effects) and an improvement in accessibility of emotion regulation strategies (medium effect). Treatment effects remained after three months follow-up. Improved acceptance of emotions and improved goal-oriented action are aspects of emotion regulation that are associated with the decrease in anxiety level. Conclusions: AT is effective in reducing anxiety symptoms, improving quality of life and aspects of emotion regulation. Future RCTs should use active controls (treatment as usual) and study cost-effectiveness.